The Effect Of Water Carry-Over In A Bank Of Industrial Coal Froth Flotation Cells With A Comparison To Laboratory Test Results - B. J. Arnold (Society for Mining, Metallurgy & Exploration, 1990)
Prior laboratory work has demonstrated -that much of the fine ash-forming minerals entering a flotation froth are there as a result of water carry-over from the bulk contents of the flotation cell (Arnold and Aplan, 1986a). Using a bank of four 300 cu ft WEMCO flotation cells cleaning a well-liberated Lower Kittanning seam coal, test results show that the sulfur and ash content of the froth is directly related to the water content of the froth (or inversely related to the percent of solids in the froth). Reagent changes which result in a watery froth produce a higher ash content in the froth. A direct comparison of laboratory and plant results show that the standard laboratory flotation test produces a product higher in sulfur and ash than that produced in the plant. Caution should be exercised when extrapolating laboratory test results to the plant situation. A method of estimating coal flotation product quality in the plant based on laboratory tests is given.